2020
DOI: 10.1038/s41467-020-14330-z
|View full text |Cite
|
Sign up to set email alerts
|

Precapillary sphincters maintain perfusion in the cerebral cortex

Abstract: Active nerve cells release vasodilators that increase their energy supply by dilating local blood vessels, a mechanism termed neurovascular coupling and the basis of BOLD functional neuroimaging signals. Here, we reveal a mechanism for cerebral blood flow control, a precapillary sphincter at the transition between the penetrating arteriole and first order capillary, linking blood flow in capillaries to the arteriolar inflow. The sphincters are encircled by contractile mural cells, which are capable of bidirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
166
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(205 citation statements)
references
References 52 publications
20
166
0
Order By: Relevance
“…The definition of the vessels, however, has varied depending on the studies. While some studies have defined all vessels including proximal and distal branches coming off penetrating arterioles as capillaries (Peppiatt et al, 2006;Hall et al, 2014;Cai et al, 2018;Khennouf et al, 2018;Grubb et al, 2020), others have defined proximal branches as precapillary arterioles (Fernández-Klett et al, 2010;Hartmann et al, 2015;Hill et al, 2015). To make matters more complicated, Hill et al (2015), have asserted that the mural cells on the proximal FIGURE 1 | Brain vessels and mural cells.…”
Section: Mural Cells In the Brain Small Vessels: Vascular Smooth Muscmentioning
confidence: 99%
See 2 more Smart Citations
“…The definition of the vessels, however, has varied depending on the studies. While some studies have defined all vessels including proximal and distal branches coming off penetrating arterioles as capillaries (Peppiatt et al, 2006;Hall et al, 2014;Cai et al, 2018;Khennouf et al, 2018;Grubb et al, 2020), others have defined proximal branches as precapillary arterioles (Fernández-Klett et al, 2010;Hartmann et al, 2015;Hill et al, 2015). To make matters more complicated, Hill et al (2015), have asserted that the mural cells on the proximal FIGURE 1 | Brain vessels and mural cells.…”
Section: Mural Cells In the Brain Small Vessels: Vascular Smooth Muscmentioning
confidence: 99%
“…Because these pericytes are positioned at the transition between arterioles and capillaries, and have shared some characteristics with SMCs, the terminology and classification of these mural cells have been hotly debated. The cells have been variably called as ensheathing pericytes Grant et al, 2019), transition/transitional pericytes (Kisler et al, 2017a;Arango-Lievano et al, 2018), pre-capillary pericytes (Zimmermann, 1923), simply 'pericytes' or 'capillary pericytes' (Hall et al, 2014;Attwell et al, 2016;Cai et al, 2018;Khennouf et al, 2018;Grubb et al, 2020), smooth muscle-pericyte hybrids (Hartmann et al, 2015;Yang et al, 2017;Dalkara, 2019), arteriole SMC (aaSMC) (Vanlandewijck et al, 2018), or pre-capillary SMCs (Hill et al, 2015). At the same time, the vessels of proximal branches coming off penetrating arterioles are also differently defined as pre-capillary arterioles (Fernández-Klett et al, 2010;Hartmann et al, 2015;Hill et al, 2015;Berthiaume et al, 2018;Erdener and Dalkara, 2019;Grant et al, 2019), post-arteriole capillaries (Gould et al, 2016) or a part of capillaries (Hall et al, 2014;Attwell et al, 2016;Cai et al, 2018;Khennouf et al, 2018;Grubb et al, 2020).…”
Section: Pericytes In the Proximal Capillariesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, using the Cspg4-Cre-Tom line, we anatomically characterized sphincter pericytes. In the brain, they control blood inflow from an artery into a capillary branch [21,38]. We found that this is a single cell fully encircling the opening into the branching vessel; the cell had relatively low SMA expression and was heavily insulated by the basement membrane.…”
Section: Mural Cell-specific Creert2 Lines For Basic Researchmentioning
confidence: 92%
“…Using the Cspg4-Cre-Tom mouse, we evaluated the sphincter cells (Figure 2i-n), a unique structure that is believed to play a role in gating blood inflow into the arterial branch [21][22][23].…”
Section: Identification Of Morphological Polarization Of Mural Cells mentioning
confidence: 99%